Review Papers in Big Data, Cloud-Based Data Analysis and Learning Systems - Talia, Domenico; Marozzo, Fabrizio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The use of advanced and scalable algorithms, along with parallel programming frameworks and high-performance computers, is commonly used to solve Big Data problems and obtain valuable information and learning processes in a reasonable time. This Special Issue includes high-quality research papers in the fields of big data, cloud-based data analysis, and machine learning systems. In particular, wide-ranging surveys and advanced research papers are included, focusing both on aspects relating to big data (e.g., frameworks for big data analysis or systems for big data management) and on the use of big data in application areas (e.g., big data from social media or big data from streams).